GROWTH-INHIBITORY EFFECTS OF CURCUMIN ON Raji CELLS AND ITS MECHANISMS - 陈燕 吴青 李新刚 (Chinese journal of cancer research, 2005)
Objective： To study the growth-inhibitory effects of curcumin on B-NHL cell line Raji cells in vitro and its molecular mechanisms. Methods： The growth inhibition rates of Raji cells, after being treated with 6.25μmol/L - 50μmol/L curcumin for 12 h - 48 h, were examined by MTT assay. The apoptosis rate was detected by flow cytometry （FCM）, the protein expression levels of bcl-2 and p53 in Raji cells were examined by SP immunohistochemistry. The expression of p53 in Raji cell were checked by RT-PCR. Results： After being treated by various concentrations of curcumin, the growth of Raji cells was inhibited significantly. The rates of apoptosis were 11.8% -79.7% （P〈0.01）, the down regulation of p53 expression was observed within 24 h after the treatment of curcumin by RT-PCR. The expression of bcl-2 and p53 was decreased, which depended on the action time. Conclusion： Curcumin could significantly inhibit the growth of Raji cells. The induction of apoptosis by down-regulating the expression of bcl-2 and p53 was probably one of its molecular mechanisms.